1985
DOI: 10.1071/sr9850095
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of pedoturbation by two species of mound-building ants, Camponotus intrepidus (Kirby) and Iridomyrmex purpureus (F. Smith)

Abstract: Details of the size, structure and occurrence of Carnponotus intrepidus nests and the size, composition and source of the mound cover on Iridomyrmex purpureus nests are reported from several areas of eastern New South Wales. Both species are common, and construct large mounds of mixed topsoil and subsoil with surface covers, which appear to protect the mound from rainsplash erosion. Camponotus thatches the mound with charcoal, leaves and twigs; Iridomyrmex covers the mound in granules of inorganic or organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Both, Gorosito et al (2006) and Cosarinsky (2006) suggested that the compact structure observed in the walls of galleries and nest chambers was necessary to stabilize the walls and to support the high mass of the Camponotus mound. Lining of nest galleries with clay or "glaze" was also reported for Trachymyrmex turrifex and Camponotus intrepidus, respectively, although its function remains elusive (Wheeler, 1907;Cowan et al, 1985). The employment of fecal matter in ant constructions or excavations has not been reported in the literature.…”
Section: Nest Micromorphology and Building Behavior In Atta Leafcuttimentioning
confidence: 90%
See 1 more Smart Citation
“…Both, Gorosito et al (2006) and Cosarinsky (2006) suggested that the compact structure observed in the walls of galleries and nest chambers was necessary to stabilize the walls and to support the high mass of the Camponotus mound. Lining of nest galleries with clay or "glaze" was also reported for Trachymyrmex turrifex and Camponotus intrepidus, respectively, although its function remains elusive (Wheeler, 1907;Cowan et al, 1985). The employment of fecal matter in ant constructions or excavations has not been reported in the literature.…”
Section: Nest Micromorphology and Building Behavior In Atta Leafcuttimentioning
confidence: 90%
“…The mound itself is not inhabited, and it results from the deposition of excavated soil during colony growth that originates from deep horizons. The mound, however, is not only a passive accumulation of excavated soil, since workers import material to reinforce and stabilize the construction, as observed for other ant species (McCook, 1877;Cowan et al, 1985), and also build structures with defined function like ventilation turrets (Jonkman, 1980b).…”
Section: Introductionmentioning
confidence: 96%
“…The surface of the mounds is often covered with a crust or mulch that can consist of sand grains, pebbles, plant fragments, or whatever coarse material is available (Scott, 1951; Mandel and Sorenson, 1982; Cowan et al, 1985). This mulch appears to be for protection from rain‐splash erosion (Cowan et al, 1985), although rain‐splash still can form a crust on the mounds during rainfall events (Mandel and Sorenson, 1982).…”
Section: Nature Of Formicarious Pedonsmentioning
confidence: 99%
“…Baxter and Hole 1967;Mandel and Sorenson 1982;Cowan et al 1985;Mitchell 1988;Lobry de Bruyn and Conacher 1990). Ants interact with soil processes by increasing soil porosity and infiltration, altering ped shape and number, reducing bulk density, regulating soil erosion by depositing subsoil on the surface, regulating plant and animal litter and concentrating organic matter around their nests (Hole 1961).…”
Section: Introductionmentioning
confidence: 99%